2017
DOI: 10.1002/2016gc006614
|View full text |Cite
|
Sign up to set email alerts
|

Olivine fabrics and tectonic evolution of fore‐arc mantles: A natural perspective from the Songshugou dunite and harzburgite in the Qinling orogenic belt, central China

Abstract: To advance our understanding of the deformation characteristics, rheological behaviors, and tectonic evolution of the fore‐arc lithospheric mantle, we analyzed mineral fabrics for a large spinel‐bearing ultramafic massif in the Songshugou area in the Qinling orogenic belt, central China. In the spinel‐poor coarse‐grained dunite, stronger A/D‐type and weaker C‐type‐like fabrics were found, whereas the spinel‐rich coarse‐grained dunite displayed a comparatively stronger B‐type‐like fabric. These olivine fabrics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 114 publications
(222 reference statements)
2
22
0
Order By: Relevance
“…The other possible mechanism for a fabric change from an A-type to B-type LPO of olivine is an enhancement of dislocation-accommodated grain boundary sliding (DisGBS) [17][18][19]86]. Precigout and Hirth [19] proposed that a fabric transition from an A-type to B-type LPO in olivine that was observed in the Ronda massif, Spain could have resulted from the enhancement of GBS as the grain size decreased.…”
Section: Development Of Lpo Of Olivinementioning
confidence: 99%
See 1 more Smart Citation
“…The other possible mechanism for a fabric change from an A-type to B-type LPO of olivine is an enhancement of dislocation-accommodated grain boundary sliding (DisGBS) [17][18][19]86]. Precigout and Hirth [19] proposed that a fabric transition from an A-type to B-type LPO in olivine that was observed in the Ronda massif, Spain could have resulted from the enhancement of GBS as the grain size decreased.…”
Section: Development Of Lpo Of Olivinementioning
confidence: 99%
“…For example, the fabric transition of olivine in the mantle wedge from an A-type to a B-type LPO of olivine is proposed as a possible mechanism for the change in the shear wave splitting pattern observed in the subduction zone [3,7,8,[12][13][14]. Many studies have proposed a hypothesis for this change in fabric: a deformation under water-rich conditions [7,8], a deformation under high pressure [10,15,16], an enhancement of grain boundary sliding [17][18][19], a diffusional creep [20], or the presence of partial melt [21,22]. There have been many reports of such fabric transitions recorded in naturally deformed peridotites from various localities: The Bergen Arc, Norway [23], the Ronda massif, Spain [19], Lien, Almklovdalen, Norway [24], the Navajo volcanic field, USA [25], and the Calatrava volcanic field, Spain [26].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that these dunites originated from the overlying NCC rather than the subducting SCB (Zheng, ). The occurrence of spinels in the Tengjia dunite and Opx porphyroblasts containing Cpx exsolved lamellae, which are similar to the Songshugou peridotite in the Qinling orogen (Cao et al, , ), suggests that the Tengjia dunites originated from the forearc mantle wedge and underwent a high degree of melt extraction under subarc conditions (Song et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Cao et al (2017) reported CPOs of olivine similar to Types C and B in Songshugou peridotites and suggested that those CPOs were formed by a diffusion-accommodated grain boundary sliding (DifGBS) at high temperatures.…”
Section: Other Possibilities For the Formation Of The Cpos Of Olivinementioning
confidence: 99%
“…Olivine is the most abundant mineral and is elastically anisotropic (Birch, 1960;Verma, 1960;Abramson et al, 1997) (Table 1). The CPO of olivine is key to understanding the seismic anisotropy and flow pattern of the upper mantle (Hess, 1964;Nicolas and Christensen, 1987;Ben Ismail and Mainprice, 1998;Jung et al, 2006;Karato et al, 2008;Cao et al, 2015;Michibayashi et al, 2016;Cao et al, 2017). In the mantle wedge and at the slab-mantle interface, hydrous minerals such as serpentine, chlorite, and amphibole can form from the fluids generated by the dehydration of hydrous minerals in the subducting slab (Ulmer and Trommsdorff, 1995;Peacock and Hyndman, 1999;Pawley, 2003;Fumagalli and Poli, 2005;van Keken et al, 2011).…”
Section: Introductionmentioning
confidence: 99%